Нылкышно саюлын: роман-чигвесь / С. В. Матвеев - Матвеев Сергей Васильевич (Удмуртия, 2020)
Экземпляры: ф.5 (2020) / Инвентарный номер: 56368 / Цена: 160.00. / Сис.шифр: К84(2Рос=Удм)-4 / Авт.знак: М 33 / ГРНТИ: 17.82.32 / ББК: 84(2=664.1)^VLBC/M